MANAJEMEN STRATEGIK DALAM MEWUJUDKAN PENDIDIKAN ISLAM YANG UNGGUL DAN BERDAYA SAING - Ndanda Ambarawadi; Chusnul Chotimah; Sulistyorini Sulistyorini (Hijri, 2025)
Strategic management in Islamic education has become a crucial aspect in facing global dynamics that demand educational institutions to excel and be competitive. This study aims to examine the concepts and practices of strategic management as an effort to improve the quality of Islamic education that is adaptive and responsive to contemporary challenges. The research method employs a literature study approach with a descriptive-analytical type, utilizing scientific literature, journals, and related documents on strategic management and Islamic education. The main findings indicate that integrating Islamic principles with modern strategic management theories can produce an effective management model in administering Islamic educational institutions. The study identifies key factors for success, such as clear planning vision, involvement of all stakeholders, and technology-based educational innovation. The conclusion emphasizes the urgency of strategic management as a foundation for the development of Islamic education that is not only academically oriented but also grounded in spiritual and character values. This study strengthens both the theoretical and practical basis for the development of excellent and competitive Islamic education management, while also opening avenues for further studies on real-world implementation.